Alfaxalone and medetomidine intravenous infusion to maintain anaesthesia in colts undergoing field castration. (25th September 2012) - Goodwin, W. A.; Keates, H. L.; Pearson, M.; Pasloske, K.
Summary: Reasons for performing the study: The use of alfaxalone and medetomidine administered as an i.v. infusion to maintain anaesthesia has not previously been reported in the horse. Objectives: To investigate the use of alfaxalone in hydroxpropyl‐beta‐cyclodextrin (Alfaxan) and medetomidine infusion as a field anaesthetic for short‐term surgical procedures in the horse. Hypothesis: Alfaxalone–medetomidine anaesthesia is suitable for short‐term field anaesthesia in horses. Methods: Eleven healthy colts underwent 45 min of anaesthesia with an i.v. infusion of alfaxalone (2 mg/kg bwt/h) and medetomidine (5 μg/kg bwt/h) for routine field castration. Horses were premedicated with i.v. acepromazine (0.03 mg/kg bwt), medetomidine (7 μg/kg bwt) and guaiphenesin (35 mg/kg bwt) before i.v. induction with alfaxalone (1 mg/kg bwt). Colts were intubated with an endotracheal tube and 100% oxygen insufflated at 10 l/min. The physiological variables monitored included pulse rate, respiratory rate, direct arterial blood pressure, arterial blood gases and the quality of the inductions and recoveries were scored. Results: Overall, the anaesthetic period and surgical conditions were acceptable and the quality of the anaesthetic inductions and recoveries was good to excellent. All colts stood on their first attempt (mean ± s.d.) 37 ± 13.5 min after the infusion was stopped. During anaesthesia, cardiopulmonary data, presented as range of mean values at each time point were: heart rate: 45–47 beats/min; mean blood pressure: 104–112 mmHg; respiratory rate: 8 breaths/min; PaO2 : 117–172 mmHg; PaCO2 : 50–56 mmHg and pH 7.34–7.37. Conclusions and potential relevance: The co‐administration of alfaxalone and medetomidine as an i.v. infusion after anaesthetic induction with alfaxalone was suitable for short‐term field anaesthesia in the horse.